(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: One of the key trends in modern medicine is downscaling and integration of complex devices. This puts a burden on the most of the existing micromanufacturing technologies. In this work we present how femtosecond (fs) based 3D micromanufacturing could benefit the field of medicine. Materials and Methods: This work was performed with “Laser Nanofactory” (Femtika) workstation. System is built around amplified fs laser source capable of widely tunable parameters. Combined with flexible focusing and easy to use software, it offers hybrid additive-subtractive 3D manufacturing capabilities. Materials used ranged from various polymers to glasses and metals. Results and Discussion: Combining additive manufacturing with subtractive processing opens new possibilities in functional structure fabrication. fs lasers are superb tool to induce both processing regimes due to diverse light-matter interaction regimes it can cause. Here it is exploited to produce prototypes of various medical devices and related structures. These include scaffolds for regenerative medicine, microneedles for drug delivery, cell perforators and miniaturized liquid flow meters. Furthermore, components for microrobots are produced out of polymers and glasses. Further challenges and capabilities of presented method are discussed, highlighting how and where it can impact development of medical devices and related structures in the future. Conclusion: In this work we demonstrated the possibility to use highly tunable amplified fs laser for hybrid additive-subtractive manufacturing in single workstation. It is exploited to perform straightforward fabrication of complex medical microdevices.